Safety Ranking of the Lithuanian Road Network of National Significance - Vilma Jasiūnienė; Donatas Čygas; Kornelija Ratkevičiūtė; Harri Peltola (The Baltic Journal of Road and Bridge Engineering)
The Directive 2008/96/EC of the European Parliament and of the Council of 19 November 2008 on Road Infrastructure Safety Management requires that the Member States shall establish and implement the network safety ranking. Safety performance of existing roads should be increased by targeting investments to the highest accident concentration sections and (or) to the road sections or crossings with the highest accident reduction potential. Road network safety management is applied within the road network in operation covering the selection of traffic safety improvement measures in optimal locations, evaluation of the safety effects and implementing the measures. The article describes the method for selecting and prioritising road sections which have higher than the average accident saving potential in each road category. When selecting road sections for treatment, a potential reduction of accident costs shall be taken into consideration. Road sections in each category are studied and classified by the factors related to road safety, such as the number of accidents, traffic flow and road characteristics. The article describes how the procedure of the road network safety ranking and the ranking of high accident concentration sections is implemented in Lithuania and propose further steps.